Quality Primary Schooling an Open Global Challenge - Shah, Sayyed Farooq (American Journal of Humanities and Social Sciences, 2015)
This article draws upon research undertaken for exploring those factors and indicators which directly or indirectly influence the primary schooling quality and explores the efforts and steps taken by UNESCO, Education For All(EFA), and WORLD DAKAR FORUM and most recently by Mellinium Development Goal(MGD) announced for 2015 as well. Relevant Data were collected from the above mentioned forums and from the teaches, head teachers, parents, policy makers, stake holders and learners to some extent, their views, expert opinions, expressions thoughts were filtered and international seminars announcements were also taken as model. At the end common view point was developed about the quality enhancing factors especially at primary level of schooling